Historic Sites during the World War II in South Konawe, Southeast Sulawesi as a Source of Historiography - Syahrun Syahrun; Rahmat Sewa Suraya; Sandy Suseno (Diponegoro University, 2022)
The World War II in Indonesian territory at that time involved the Imperial Japanese Army against the military from the allies and was known later as “Theater of Pacific”. The massive military activities that took place in Indonesian territory during the World War II definitely left a lot of and varied material evidences. However, in fact, many of the material evidences from the World War II have been forgotten due to its dilapidated condition. One of the military operational areas where many evidences of the World War II can be found is South Konawe, precisely at Kendari II Airfield Site, which is now known as HLO Airfield (Halu Oleo Airfield). This research utilized archives and aerial photographs during the World War II combined with direct observation at the site and reconstruction efforts using excavated data. Based on the findings, it reveals the existence of the World War II remains at Kendari II Airfield area. It is also known that the condition of the most massive findings is located in the Japanese military administration and maintenance area during the World War II at Kendari II Airfield area. These remains can certainly be a source of historical writing of the Japanese Government Era in South Konawe.